(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cloud computing is the delivery of different computing services over the internet (‘the cloud’) such as - software, analytics, servers, storage, databases, networking, and intelligence to offer faster innovation, flexible resources, and economies of scale. The amount is typically paid only for cloud services we use, helping lower our operating costs, run infrastructure more efficiently and scale as our business needs change. Affordable, efficient, and scalable, cloud computing is still the best solution for most businesses – but it can still leave us vulnerable if the proper precautions aren’t taken.Managers have traditionally viewed IT as difficult and expensive and the promise of cloud computing leads many to think that IT will now be easy and cheap. The reality is that cloud computing has simplified some technical aspects of building computer systems, but the myriad challenges facing IT environment still remain. Organizations which consider adopting cloud based services must also understand the many major problems of information policy, including issues of privacy, security, reliability, access, and regulation. The goal of this article is to identify the main security issues and to draw the attention of both decision makers and users to the potential risks of moving data into “the cloud”. Cloud computing services cover a vast range of options now, from the basics of storage, networking, and processing power through to natural language processing and artificial intelligence as well as standard office applications. Pretty much any service that doesn’t require you to be physically close to the computer hardware that you are using can now be delivered via the cloud.